The Changing Scenario of Agriculture - Prem Narain (Journal of Agronomy Research, 2017)
This perspective reviews shifts in agriculture driven by technology, market forces, and climate pressures. It discusses productivity trends, resource constraints, and the transition toward sustainable, resilient practices. The article outlines policy and research priorities to balance yields with environmental stewardship and rural livelihoods.
Keywords: Agriculture